Peran Notaris Dalam Pendirian Perseroan Terbatas Pasca Undang-Undang Cipta Kerja - Andhita Dewi, Putu Inten; Novy Purwanto, I Wayan (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 6 No 03 (2021)DO - 10.24843/AC.2021.v06.i03.p7, 2021)
Abstract This writing aims to analyze, examine and elaborate on the role of a Notary in the establishment of a Limited Company as stipulated in the Law on Limited Liability Companies and also the role of a Notary in the establishment of a Limited Company after the enactment of the Law on Job Creation. This is normative legal research method using statute approach, conceptual approach, and analytical approach. The results show that Article 7 of the Limited Liability Company Law requires the establishment of a Limited Company based on a notarial deed, this explicitly determines the role of a Notary in the establishment of a Limited Company. The enactment of the Job Creation Law provides a change in the concept of Limited Company, which can now be formed by individuals in accordance with the criteria for Micro and Small Enterprises based on the Statement of Establishment. However, the Job Creation Law stipulates that in the case that an individual PT does not meet the criteria as a Micro and Small Enterprises, the Limited Company must change its status in accordance with the Limited Liability Company Law and use a notarial deed as the basis for the establishment of the Limited Company. Hence, the role of the Notary is still required to make a notarial deed if the Individual Company changes the status of the Company in accordance with the Company Law. Abstrak Penelitian ini bertujuan untuk menganalisis, mengkaji dan mengelaborasi peranan Notaris dalam pendirian PT sebagaimana ditentukan dalam UU PT dan juga peranan Notaris dalam pendirian PT pasca diundangkannya UU Cipta Kerja. Tulisan ini menggunakan metode penelitian hukum normatif dengan menggunakan pendekatan peraturan perundang-undangan (statute approach), pendekatan konsep (conceptual approach), serta pendekatan analisis (analytical approach). Hasil penelitian menunjukkan bahwa Pasal 7 UU Perseroan Terbatas mewajibkan pendirian PT diDasarkan pada akta notaris, hal ini secara eksplisit menentukan peran Notaris dalam pendirian PT. Pemberlakuan UU Cipta Kerja memberikan perubahan dalam konsep PT yang sekarang dapat dibentuk oleh perorangan sesuai dengan kriteria Usaha Mikro dan Kecil yang berdasarkan pada Pernyataan Pendirian. Tetapi, UU Cipta Kerja menentukan bahwa dalam PT Perorangan tidak memenuhi kriteria sebagai UMK, maka PT tersebut harus mengubah statusnya sesuai dengan UU PT dan menggunakan akta notaris sebagai dasar pendirian PT. Peran Notaris tetap dibutuhkan untuk membuat akta notaris apabila PT Perorangan mengubah status Perseroan sesuai dengan UU PT.